THE DEVELOPMENT OF SCHOOL LIBRARIES TO ENCOURAGE THE LITERACY CULTURE OF THE YOUNGER GENERATION IN KOPENG VILLAGE, GETASAN DISTRICT, SEMARANG REGENCY - Fahlefi, Diva Riza; Bowo, Prasetyo Ari (Universitas Negeri Semarang, 2021)
The quality of basic education in remote areas, especially in Kopeng Village, is far from expected. This can be seen from the low participation of access to education, limited educational facilities and infrastructure, lack of educational social media, low social relations and communication, low motivation of educational participation, lack of utilization of educational resources, lack of availability of tutoring, low educational entertainment, the variety of educational games that are still very limited and the lack of increased learning with nature. This condition will also definitely give birth to a very conventional learning nuance. Departing from the empirical facts above, it is necessary to design a comprehensive program to advance basic education in Kopeng Village by developing school libraries to encourage the literacy culture of the younger generation in the village through the socialization of literacy movements for students, the establishment of smart houses to strengthen the function of regional libraries and conduct diligent reading movements for the people in the village. The role of libraries in education is very important, namely to help the implementation of education well. School libraries will be useful if it facilitates the achievement of the goals of the teaching and learning process in schools. Indications of these benefits are not only in the form of high achievement of students, but furthermore, among others, students can find, find, filter and assess information, students are accustomed to self-study, students are trained towards responsibility, students are always following the development of science and technology, and so on. Kualitas pendidikan dasar di daerah terpencil khususnya di Desa Kopeng masih jauh dari harapan. Hal ini dapat dilihat dari rendahnya partisipasi akses pendidikan, keterbatasan sarana dan prasarana edukasi, kurangnya media sosial edukasi, rendahnya hubungan sosial dan komunikasi, rendahnya motivasi partisipasi pendidikan, kurangnya pemanfaatan sumber pendidikan, belum tersedianya bimbingan belajar, rendahnya hiburan edukasi, ragam permainan edukasi yang masih sangat terbatas dan kurang adanya peningkatan belajar dengan alam. Kondisi tersebut juga pasti akan melahirkan nuansa belajar yang sangat konvensional. Berangkat dari fakta empiris di atas maka perlu untuk merancang sebuah program yang komprehensif dalam rangka memajukan pendidikan dasar di Desa Kopeng dengan melakukan pengembangan perpustakaan sekolah untuk mendorong budaya literasi generasi muda di desa tersebut melalui sosialisasi gerakan literasi untuk siswa, pembentukan rumah pintar untuk memperkuat fungsi perpustakaan daerah serta melakukan gerakan rajin membaca untuk masyarakat di desa tersebut. Peranan perpustakaan di dalam pendidikan amatlah penting, yaitu untuk membantu terselenggaranya pendidikan dengan baik. Perpustakaan sekolah akan bermanfaat apabila benar-benar memperlancar pencapaian tujuan proses belajar mengajar di sekolah. Indikasi manfaat tersebut tidak hanya berupa tingginya prestasi murid-murid, tetapi lebih jauh lagi, antara lain adalah murid-murid mampu mencari, menemukan, menyaring dan menilai informasi, murid-murid terbiasa belajar mandiri, murid-murid terlatih ke arah tanggung jawab, murid-murid selalu mengikuti perkembangan ilmu pengetahuan dan teknologi, dan sebagainya.